Mechanical properties of multi jet fusion-printed polyamide 12 composites reinforced by glass beads and glass fibres - Chan, Jacob Wei Xuan (Nanyang Technological University, 2022)
Additive manufacturing (AM) techniques have been developing rapidly over the years. One such technique is the Multi Jet Fusion (MJF), which is relatively new that was created in the past decade. With its high printing speed, it offers many benefits. However, its main material polyamide 12 (PA12) does not have sufficient mechanical performance to use for certain load bearing applications. In this work, the mechanical performance of MJF printed glass fibres (GF) and glass beads (GB) reinforce PA12 composites is investigated. Results revealed that the addition of GB could reduce the degree of anisotropy in GF/PA12 specimens. Further testing of other weight fractions of GB/GF/PA12 shows that the GB could indeed reduce the degree of anisotropy, but the decrease of porosity shows that there is a drop in the ultimate tensile strength (UTS). It was also observed that the printing parameters of GF/PA12 is not suitable for GF/GB/PA12 and there is a need for further optimization of the printing parameters. This work provides a guidance for the printing of PA12 composites reinforcement.